Consumption of echium oil increases EPA and DPA in blood fractions more efficiently compared to linseed oil in humans. Issue 1 (December 2016) - Kuhnt, Katrin; Weiß, Stefanie; Kiehntopf, Michael; Jahreis, Gerhard
Abstract Background A plant-based strategy to improve long-chain (LC) omega (n)-3 PUFA supply in humans involves dietary supplementation with oils containing α-linolenic acid (ALA) alone or in combination with stearidonic acid (SDA). The study aimed to compare the effects of echium oil (EO) and linseed oil (LO) on LC n-3 PUFA accumulation in blood and on clinical markers. Methods In two double-blind, parallel-arm, randomized controlled studies, all volunteers started with 17 g/d run-in oil (2 weeks). Thereafter, subjects received diets enriched in study 1 with EO (5 g ALA + 2 g SDA; n = 59) or in study 2 with LO (5 g ALA; n = 59) daily for 8 weeks. The smaller control groups received fish oil (FO; n = 19) or olive oil (OO; n = 18). Participants were instructed to restrict their dietary n-3 PUFA intake throughout the studies (e.g., no fish). To investigate the influence of age and BMI on the conversion of ALA and SDA as well as clinical markers, the subjects recruited for EO and LO treatment were divided into three subgroups (two age groups 20–35 y; 49–69 y with BMI 18–25 kg/m2 and one group with older, overweight subjects (age 49–69 y; BMI >25 kg/m2 ). Results In plasma, red blood cells (RBC), and peripheral blood mononuclear cells (PBMC), EPA and docosapentaenoic acid (DPA) were ~25 % higher following EO compared to LO. Comparing all treatments, the effectiveness of increasing EPA and DPA in plasma, RBC, and PBMC was on average 100:25:10:0 and 100:50:25:0 for FO:EO:LO:OO, respectively. EO led to a lower arachidonic acid/EPA-ratio compared to LO in plasma, RBC, and PBMC. Following EO, final DHA was not greater compared to LO. Higher BMI correlated negatively with increases in plasma EPA and DPA after EO supplementation, but not after LO supplementation. Decreasing effect on plasma LDL-C and serum insulin was greater with EO than with LO. Conclusions Daily intake of SDA-containing EO is a better supplement than LO for increasing EPA and DPA in blood. However, neither EO nor LO maintained blood DHA status in the absence of fish/seafood consumption. Trial registration ClinicalTrials.gov Reg No.NCT01856179 ; ClinicalTrials.gov Reg No.NCT01317290 .